Can measures of social cognition predict autistic traits? - Juan Carlos Oliveros; Idalmis Santiesteban; José Luis Ulloa (Acta Psychologica, 2023)
Past research has yielded conflicting findings concerning socio-cognitive deficits in individuals with autistic traits. This raises the fundamental question whether autistic traits and socio-cognitive abilities are related. The present study investigated whether three key socio-cognitive abilities—imitation-inhibition, empathy, and emotion regulation—can serve as predictive factors for autistic traits within a neurotypical population. Participants (N = 166, Mage = 24.83 years, SDage = 5.20 years, rangeage = 18 to 39 years) were asked to perform an online imitation-inhibition task and complete self-report measures assessing empathy, emotion regulation, and autistic traits. Empathy was measured using the Interpersonal Reactivity Index (IRI), emotion regulation was assessed using the Difficulties in Emotion Regulation Scale (DERS), and autistic traits were measured using the ten-item short form of the Autism-Spectrum Quotient (AQ-10). Multiple regression analyses revealed that both imitation-inhibition and emotion regulation were significantly associated with autistic traits. However, empathy was not found to be a significant predictor. Our study aimed to clarify inconsistent results regarding the relationship between socio-cognitive abilities and autistic traits.